2014
DOI: 10.1111/jmft.12080
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Education in Community Settings: Effectiveness with Distressed and Non‐Distressed Low‐Income Racial Minority Couples

Abstract: Couple relationship education (CRE) programs are intended to prevent negative couple outcomes, however, some evidence suggests couples in greater distress may still benefit. The current study examined pre- and postchanges in relationship functioning of 362 low-income African American and Hispanic couples. Outcomes (dedication and communication) were assessed by examining differences between two distinct groupings of couples; distressed (both partners reporting clinically significant distress) and nondistressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 59 publications
8
45
1
3
Order By: Relevance
“…Our results are consistent with previous studies that demonstrated that RE improved participants' overall conflict (Rhoades, ) and that providing RE to one member of a couple, or someone not in a current relationship, is beneficial (Rhoades & Stanley, ) and perhaps a safer approach than providing RE to both members of a couple. Moreover, the results of our study add to the growing body of literature indicating that RE may be more effective for couples and individuals who begin with greater levels of distress (Amato, ; Carlson, Rappleyea, et al, ; Quirk, Strokoff, Owen, France, & Bergen, ; Rhoades, ). Our findings indicated that no significant differences existed on any construct of interest for participants in the no violence group.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results are consistent with previous studies that demonstrated that RE improved participants' overall conflict (Rhoades, ) and that providing RE to one member of a couple, or someone not in a current relationship, is beneficial (Rhoades & Stanley, ) and perhaps a safer approach than providing RE to both members of a couple. Moreover, the results of our study add to the growing body of literature indicating that RE may be more effective for couples and individuals who begin with greater levels of distress (Amato, ; Carlson, Rappleyea, et al, ; Quirk, Strokoff, Owen, France, & Bergen, ; Rhoades, ). Our findings indicated that no significant differences existed on any construct of interest for participants in the no violence group.…”
Section: Discussionsupporting
confidence: 64%
“…Yet, researchers have noted a demographic shift toward more highly distressed participants attending RE programs (A. B. Bradford et al, ; Carlson, Rappleyea, et al, ; Quirk et al, ). Similarly, although individuals experiencing IPV were not the targeted population of our study, most participants (71.7%) reported some or a severe level of violence in their current or most recent relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, overall effect sizes for large-scale, non-university based relationship education programs tend to be small regardless of rigor or dosage, as evidenced in the Building Strong Families (BSF) and Healthy Marriage Initiative projects (e.g., Johnson, 2012;Wood, McConnell, Moore, Clarkwest, & Hsueh, 2012). As to why effect sizes are typically small among prevention programs in general, some researchers posit that prevention/relationship education programs are able to reach a large percentage of non-distressed couples who may be less likely to use tools learned in these interventions and also report more satisfaction at baseline, which creates a ceiling effect in assessing change over time (Doss et al, 2016;Quirk, Strokoff, Owen, France, & Bergen, 2014). Thus, specifically targeting moderately distressed couples in future research may aid in improving overall effect sizes as these couples might be more motivated to apply the skills learned and have greater opportunity to evince change in relationship satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As to why effect sizes are typically small among prevention programs in general, some researchers posit that prevention/relationship education programs are able to reach a large percentage of non-distressed couples who may be less likely to use tools learned in these interventions and also report more satisfaction at baseline, which creates a ceiling effect in assessing change over time (Doss et al, 2016;Quirk, Strokoff, Owen, France, & Bergen, 2014). Consistent with this suggestion and with previous research Hawkins & Erickson, 2015;Quirk et al, 2014), in the present study distressed couples evidenced the greatest treatment gains, whereas non-distressed couples reported small effects. Consistent with this suggestion and with previous research Hawkins & Erickson, 2015;Quirk et al, 2014), in the present study distressed couples evidenced the greatest treatment gains, whereas non-distressed couples reported small effects.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of RE for low-income couples found that greater percentage of the sample initially in the distressed range was associated with larger effects at post treatment (Hawkins & Erickson, 2015); unfortunately, follow-up analyses were not included. Recent RE studies that have examined whether initial satisfaction predicts changes over follow-up have yielded mixed results, with some studies showing RE was more effective for unhappier couples (Halford et al, 2017; Quirk, Strokoff, Owen, France, & Bergen, 2014) while other studies found that initial satisfaction did not moderate intervention effects (Trillingsgaard, Fentz, Hawrilenko, & Cordova, 2016). …”
Section: Introductionmentioning
confidence: 99%